Konsep Dasar Pendidikan Islam: Perspektif Al-Quran, Al- Hadis, Filosofis, Yuridis Formal, Psikologis, Dan Sosiologis - Siddik, Hasbi; Syahrul, Syahrul (LPPM IAIN Sorong, 2022)
This article seeks to raise the foundation or basic concepts of Islamic education in the Qur'an, Hadith, philosophy, formal juridical, psychological, and sociological. The basic concepts of Islamic education can be found in the Qur'an, namely: First, the object of education is Adam or humans. The second is Islamic education material. The third is the teaching method. Fourth is the value or benefit of education. Fifth, seeking knowledge is an obligation. The basic concept of Islamic Education The hadith perspective illustrates that basically a Muslim and Muslimat are ordered to provide education and explain some of the benefits of teaching science to others. While the basis of Islamic education from a philosophical perspective is the formation of noble character, Islam stipulates that moral education is the soul of Islamic education. Furthermore, from a formal juridical perspective, the basic concept of Islamic education has a strong legal umbrella that is protected by the state. Furthermore, the concept of Islamic education in the perspective of Psychology views that education is something fundamental in human life, with human education it can develop and vice versa, without learning humans cannot develop. While the sociological basis that Islamic education is an activity that contains a process of interaction between two or more individuals and even two generations, which have the opportunity to develop themselves.